2015
DOI: 10.1002/2014wr016321
|View full text |Cite
|
Sign up to set email alerts
|

Video observations of bed form morphodynamics in a meander bend

Abstract: A new optical remote sensing technique for estimating water depth from an oblique camera view is described. The water surface and the bed were imaged simultaneously to create time-dependent maps of the water surface velocities and the bed elevations that can be used to validate numerical models at high spatial and temporal resolution. The technique was applied in a sandy meander bend at the University of Minnesota Saint Anthony Falls Laboratory Outdoor StreamLab. The root mean square differences between optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Although global reanalysis or numerical modeling may provide a more detailed wave characterization, use of available regional climate models (e.g., The Medatlas Group, 2004) is easier and may represent a valid alternative. Further, the dynamics of the nearshore area before, during and after storm events could also be inspected by means of novel devices like: (i) Lagrangian drifters, capable of measuring both three-dimensional hydrodynamics and seabed depth (e.g., Postacchini et al, 2016a), (ii) videomonitoring systems, like that available at the Senigallia harbor since 2015, to reconstruct the coastline (e.g., Archetti, 2009;Vousdoukas et al, 2011;Archetti et al, 2016), as well as wave field and bed morphology (e.g., Palmsten et al, 2015) and (iii) radar images, like those used for the reconstruction of both wave field and bathymetry, through the depth inversion technique (e.g., Ludeno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although global reanalysis or numerical modeling may provide a more detailed wave characterization, use of available regional climate models (e.g., The Medatlas Group, 2004) is easier and may represent a valid alternative. Further, the dynamics of the nearshore area before, during and after storm events could also be inspected by means of novel devices like: (i) Lagrangian drifters, capable of measuring both three-dimensional hydrodynamics and seabed depth (e.g., Postacchini et al, 2016a), (ii) videomonitoring systems, like that available at the Senigallia harbor since 2015, to reconstruct the coastline (e.g., Archetti, 2009;Vousdoukas et al, 2011;Archetti et al, 2016), as well as wave field and bed morphology (e.g., Palmsten et al, 2015) and (iii) radar images, like those used for the reconstruction of both wave field and bathymetry, through the depth inversion technique (e.g., Ludeno et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These questions are far from being answered in existing studies. Moreover, some studies [e.g., Bohorquez et al ., ; Palmsten et al ., ] reported that bed form as ripples and dunes in river bends can increase the effective roughness height and total shear stress at both lab and field scales. It should be noted that in turn this can further affect hydrodynamics and morphodynamics at the bend.…”
Section: Introductionmentioning
confidence: 99%
“…The use of UAVs and aerial images has improved our ability to quantify the spatial organisation of river relief and bed roughness (Williams et al, 2014;Dietrich, 2016;James et al, 2017;Carbonneau et al, 2018), to track morphological change over short time periods (Lane et al, 1996(Lane et al, , 2010Palmsten et al, 2015) and to infer sediment transport rates (Lane et al, 1995;Brasington et al, 2003;Vericat et al, 2017). However, a number of outstanding challenges remain.…”
Section: Introductionmentioning
confidence: 99%